How Long Do We Live?
XIV, 284 p. 58 illus.
Keywords: The most widely used measure of longevity is the period life expectancy at birth which is calculated from age specific death rates by life table methods. In 2002, John Bongaarts and Griffith Feeney introduced the revolutionary idea that this conventional estimate of period life expectancy is distorted by a tempo effect whenever longevity is changing. The tempo effect is defined as an inflation or deflation of the period incidence of a demographic event resulting from a rise or fall in the mean age at which the event occurs. Some demographers agree with this radical argument; others disagree. The book reviews the debate on how best to measure period longevity. In the various chapters, leading experts in demography critically examine the existence of the tempo effect in mortality, present extensions and applications, and compare period and cohort longevity measures. The book provides a deeper understanding of and new insights into the fundamental question "How long do we live"?